2011
DOI: 10.1002/elan.201000657
|View full text |Cite
|
Sign up to set email alerts
|

How to Determine Uranium Faster and Cheaper by Adsorptive Stripping Voltammetry in Water Samples Containing Surface Active Compounds

Abstract: A modification of the voltammetric procedure for the determination of uranium in the presence of cupferron using hanging mercury drop electrode is presented. The pulsed potential accumulation was proposed for the minimization of interferences of surface active substances. The calibration plot for U(VI) in the presence of 2 ppm Tritonu X-100 was linear from 1.7 10 À10 to 2.0 10 À8 mol L À1 for an accumulation time of 60 s, with correlation coefficient of 0.996. The application of this method was tested in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…Cupferron is widely used in analytical chemistry forming stable complexes with a lot of metals which willingly adsorb onto the mercury electrode. We can find numerous adsorptive stripping procedures which employ cupferron as a complexing agent for sensitive determinations of many metals, such as aluminum [34,35], chromium [36,37], copper [38], vanadium [39], titanium [40], europium [41], molybdenum and uranium [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Cupferron is widely used in analytical chemistry forming stable complexes with a lot of metals which willingly adsorb onto the mercury electrode. We can find numerous adsorptive stripping procedures which employ cupferron as a complexing agent for sensitive determinations of many metals, such as aluminum [34,35], chromium [36,37], copper [38], vanadium [39], titanium [40], europium [41], molybdenum and uranium [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that U(VI) and Bi(III) form electrochemically active stable complexes with cupferron, which makes voltammetric determination of these elements with a low detection limit possible (Kefala et al 2006; Korolczuk et al 2007; Grabarczyk and Koper 2011a, b; Koper and Grabarczyk 2011). The proposed procedure concentrated on the selection of optimum conditions for the simultaneous determination of uranium and bismuth in one voltammetric scan.…”
Section: Resultsmentioning
confidence: 99%
“…As a supporting electrolyte, an acetate buffer was chosen on the basis of literature data (Korolczuk et al 2007; Grabarczyk and Koper 2011a, b; Koper and Grabarczyk 2011) as the most suitable both for U(VI)–cupferron and Bi(III)–cupferron complex formation and accumulation on the working electrode. The pH of the supporting electrolyte was changed from 3 to 6, and its influence on uranium and bismuth peak currents is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that major sources of interferences in U(VI)-cupferron complex current were likely to be the nonionic surfactants such as Triton X-100, which can cause a 55% decay of the UO 2 2+ peak at the concentration of 2 mg L À1 . Considering the fact that natural water samples typically contain surfactants similar to 0.01-2 mg L À1 of Triton X-100 [60,61], it can be assured that the proposed method in The inset is the fitted curve of UO 2 2+ measurement obtained from standard addition.…”
Section: Study Of Interferencesmentioning
confidence: 99%